2022
DOI: 10.3390/s22052072
|View full text |Cite
|
Sign up to set email alerts
|

Naked-Eye Detection of Morphine by Au@Ag Nanoparticles-Based Colorimetric Chemosensors

Abstract: In this study, we report a novel and facile colorimetric assay based on silver citrate-coated Au@Ag nanoparticles (Au@AgNPs) as a chemosensor for the naked-eye detection of morphine (MOR). The developed optical sensing approach relied on the aggregation of Au@Ag NPs upon exposure to morphine, which led to an evident color variation from light-yellow to brown. Au@Ag NPs have been prepared by two different protocols, using high- and low-power ultrasonic irradiation. The sonochemical method was essential for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The developed sensor boasts an impressive linear range that spans from 0.008 to 40 ppm, a range that is more extensive than nearly all other methods considered, including GC-MS (0.0025–2 ppm) [ 138 ], surface plasmon resonance imaging (1–50 ppm) [ 142 ], colorimetric assay (19.97–856 ppb) [ 143 ], piezoelectric sensor (0.25–2500 ppb) [ 140 ], and various other sensor types [ 62 , 139 , 141 , 146 ]. This practical broader linear range enhances the versatility and adaptability of our sensor for use with a wide range of concentration levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed sensor boasts an impressive linear range that spans from 0.008 to 40 ppm, a range that is more extensive than nearly all other methods considered, including GC-MS (0.0025–2 ppm) [ 138 ], surface plasmon resonance imaging (1–50 ppm) [ 142 ], colorimetric assay (19.97–856 ppb) [ 143 ], piezoelectric sensor (0.25–2500 ppb) [ 140 ], and various other sensor types [ 62 , 139 , 141 , 146 ]. This practical broader linear range enhances the versatility and adaptability of our sensor for use with a wide range of concentration levels.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of methods have been developed for the detection of controlled and illicit drugs; they mainly include high-performance liquid chromatography (HPLC) [ 45 , 46 , 47 ], gas chromatography mass spectrometry (GCMS) [ 48 , 49 , 50 ], electrochemical sensors [ 7 , 51 , 52 ], electrochemical luminescence [ 53 , 54 , 55 ], fluorescence spectroscopy [ 56 , 57 ], and surface-enhanced Raman spectroscopy (SERS) [ 58 , 59 , 60 ]. However, these methods have certain shortcomings, such as a complexity in analysis, the need for highly trained operators, long pre-treatment periods, and high costs [ 59 , 61 , 62 ]. Fluorescence spectroscopy, with the aid of chemical fluorophores or biochemical aptamers, stands out as a promising detection technique that can overcome the limitations of the mentioned methods.…”
Section: Introductionmentioning
confidence: 99%
“…This advancement effectively addresses the challenges of identifying illicit drugs in intricate biological samples, presenting enhanced functionality and dependability. Incorporation of nanomaterials, such as metal nanoparticles [133][134][135], carbon nanomaterials [136,137], and quantum dots [138], has dramatically enhanced the sensitivity of colorimetric sensors. Nanomaterials provide a large surface area for interactions with target analytes, leading to increased signal amplification and improved sensor response at lower concentrations of opioids.…”
Section: Colorimetric Detectionmentioning
confidence: 99%
“…This potency was reduced in the presence of Hg 2+ ions, which were employed to detect Hg 2+ ions in aqueous systems using the naked eye and spectrophotometry [5]. Bastami et al prepared silver citrate-coated Au@Ag nanoparticles and demonstrated their ability in detecting morphine using the naked eye and using the change in color from light yellow to brown [6].…”
Section: Introductionmentioning
confidence: 99%